Learning from ambiguously labeled examples - Hüllermeier, Eyke; Beringer, J. (Intelligent Data Analysis)

Physicochemical descriptors to discriminate protein interactions in permanent and transient complexes by means of machine learning algorithms - Block, P.; Paern, J.; Hüllermeier, Eyke; Sanschagrin, P.; Sotriffer, C.; Klebe, G. (Proteins: Structure, Function and Bioinformatics)

From the similarity analysis of protein cavities to the functional classification of protein families using Cavbase - Kuhn, D.; Weskamp, N.; Schmitt, S.; Hüllermeier, Eyke; Klebe, G. (Journal of Molecular Biology)

Online clustering of parallel data streams - Beringer, J.; Hüllermeier, Eyke (Data and Knowledge Engineering)

A fuzzy-probablistic earthquake risk assessment system - Karimi, I.; Hüllermeier, Eyke; Meskouris, K. (Soft Computing)

"Wir haben ein Gesetz...!" rechtliche Anmerkungen zum Strafverfahren gegen Jesus - Krimphove, Dieter

Production engineering for video based e- and m-learning content - Herzog, Michael A.; Trier, Matthias; Sieck, Jürgen (Proceedings of UNESCO International Centre for Engineering Education (UICEE) 10th Baltic Seminar on Engineering Education)

Towards a Social Network Intelligence Tool for visual Analysis of Virtual Communication Networks - Trier, Matthias (Virtuelle Organisationen und Neue Medien)

Erratum to „Reductions of Symmetry configurations n3 - Boben, Marco; Pisanski, Tomaž; Ravnik, Natasa; Steffen, Eckhard (Discrete Applied Mathematics)

Executing Hardware Tasks on Dynamically Reconfigurable Devices under Real-time Conditions - Danne, Klaus; Mühlenbernd, Roland; Platzner, Marco (Proceedings of the 16th International Conference on Field Programmable Logic and Applications (FPL))

An EDF Schedulability Test for Periodic Tasks on Reconfigurable Hardware Devices - Danne, Klaus; Platzner, Marco (In ACM SIGPLAN/SIGBED Conference on Languages, Compilers, and Tools for Embedded Systems (LCTES))

Partitioned Scheduling of Periodic Real-time Tasks onto Reconfigurable Hardware - Danne, Klaus; Platzner, Marco (Proceedings of the 13th Reconfigurable Architectures Workshop (RAW))

Experimental and theoretical evidence for a hydrogen stabilizedc(2×2)reconstruction of the P-rich InP(001) surface - Letzig, T.; Willig, F.; Hahn, P. H.; Schmidt, Wolf Gero (Physical Review B)

Clean and pyrrole-functionalized Si- and C-terminated SiC surfaces: First-principles calculations of geometry and energetics compared with LEED and XPS - Preuss, M.; Bechstedt, F.; Schmidt, Wolf Gero; Sochos, J.; Schröter, B.; Richter, W. (Physical Review B)

Organic molecule adsorption on solid surfaces: chemical bonding, mutual polarisation and dispersion interaction - Schmidt, Wolf Gero; Seino, K.; Preuss, M.; Hermann, A.; Ortmann, F.; Bechstedt, F. (Applied Physics A)

Adsorption of phenylglycine on copper: Density functional calculations - Blankenburg, S.; Schmidt, Wolf Gero (Physical Review B)

Structure, energetics, and vibrational spectra of perylene adsorbed on Si(001): First-principles calculations compared with STM and HREELS - Preuss, M.; Miotto, R.; Bechstedt, F.; Rada, T.; Richardson, N. V.; Schmidt, Wolf Gero (Physical Review B)

Strongly bonded water monomers on the ice Ih basal plane: Density-functional calculations - Thierfelder, C.; Hermann, A.; Schwerdtfeger, P.; Schmidt, Wolf Gero (Physical Review B)

Adsorption of water on chlorine-terminated Si(111) from first principles: Substrate-induced ordering versus intermolecular interactions - Biering, S.; Hermann, A.; Schmidt, Wolf Gero (Physical Review B)

Si(001) surface optical anisotropies induced by π-conjugated overlayers and oxidation - Schmidt, Wolf Gero; Hermann, A.; Fuchs, F.; Bechstedt, F. (Current Applied Physics)

Si(001) c(4×2)–p(2×2) surface phase transitions induced by electric fields and doping - Schmidt, Wolf Gero; Seino, K. (Current Applied Physics)

Ga-richGaAs(001)surface fromab initiocalculations: Atomic structure of the(4×6)and(6×6)reconstructions - Seino, K.; Schmidt, Wolf Gero; Ohtake, A. (Physical Review B)

Molecular electronic excitations calculated from a solid-state approach: Methodology and numerics - Hahn, P. H.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Semiempirical van der Waals correction to the density functional description of solids and molecular structures - Ortmann, F.; Bechstedt, F.; Schmidt, Wolf Gero (Physical Review B)

Aus dem Englischen ins Italienische: M. Cohen, Wittgestein’s Beetle and Other Thought Experiments

Asmuth, Christoph, Interpretation – Transformation, Vandenhoeck&Ruprecht, Amsterdam - Ficara, Elena (Rivista di Filosofia)

Die Ontologie in der „Kritik der reinen Vernunft“ - Ficara, Elena

Comparison of Performance and Realization Effort of a Very Sparse Matrix Converter to a Voltage DC Link PWM Inverter with Active Front End - Round, Simon; Schafmeister, Frank; Kolar, Johann (IEEJ Transactions of the Institute of Electrical Engineers of Japan)

Transient peak currents in permanent magnet synchronous motors for symmetrical short circuits - Meyer, M.; Böcker, Joachim (International Symposium on Power Electronics, Electrical Drives, Automation and Motion, 2006. SPEEDAM 2006.)

Energy Management for an Onboard Storage System Based on Multi-Objective Optimization - Knoke, Tobias; Romaus, Christoph; Böcker, Joachim; Dell'Aere, Alessandro; Witting, Katrin (IECON 2006 - 32nd Annual Conference on IEEE Industrial Electronics)

Modelling and Control of a Multi-Mass Ultrasonic Motor for Airborne Applications - Wetzel, H.; Fröhleke, N.; Böcker, Joachim; Ouchouche, S.; Bezanere, D.; Cugnon, F. (IECON 2006 - 32nd Annual Conference on IEEE Industrial Electronics)

Self-Optimization as a Framework for Advanced Control Systems - Böcker, Joachim; Schulz, Bernd; Knoke, Tobias; Fröhleke, Norbert (IECON 2006 - 32nd Annual Conference on IEEE Industrial Electronics)

Investigation of Power Supplies for a Piezoelectric Brake Actuator in Aircrafts - Li, Rongyuan; Fröhleke, Norbert; Wetzel, Hermann; Böcker, Joachim (2006 CES/IEEE 5th International Power Electronics and Motion Control Conference)

High Efficient 3kW Three-Stage Power Supply - Wetzel, H.; Fröhleke, N.; Böcker, Joachim; Ide, P. (Twenty-First Annual IEEE Applied Power Electronics Conference and Exposition, 2006. APEC '06.)

Advanced convoy control strategy for autonomously driven railway vehicles - Henke, C.; Fröhleke, Norbert; Böcker, Joachim (2006 IEEE Intelligent Transportation Systems Conference)

Drive Control and Position Measurement of RailCab Vehicles Driven by Linear Motors - Pottharst, A.; Henke, C.; Schneider, T.; Böcker, Joachim; Grotstollen, H. (Int. Symposium on Instrumentation and Control Technology (ISICT), Beijing, China)

Redundante Positionserfassung für ein spurgeführtes linearmotorgetriebenes Bahnfahrzeug - Schneider, T.; Schulz, B.; Henke, C.; Böcker, Joachim (Workshop Entwurf mechatronischer Systeme, Heinz-Nixdorf-Institut, Universität Paderborn,)

Optimum Control for Interior Permanent Magnet Synchronous Motors (IPMSM) in Constant Torque and Flux Weakening Range - Meyer, Michael; Böcker, Joachim (2006 12th International Power Electronics and Motion Control Conference)

Psychologism and the Distinction between Discovery and Justification - Peckhaus, Volker (Revisiting Discovery and Justification. Historical and Philosophical Perspectives on the Context Distinction)

Der Baum der Erkenntnis - Peckhaus, Volker (Die besten Nebenrollen. 50 Porträts biblischer Randfiguren)

Predeductive Reasoning - Peckhaus, Volker (Demonstrative and Non-demonstrative Reasoning in Mathematics and Natural Sciences. Workshop University of Rome ‘La Sapienza’, Rome, Villa Mirafiori, 16-17 June 2005)

Die Aktualität der Logik als Organon - Peckhaus, Volker (Kreativität. XX. Deutscher Kongress für Philosophie. 26.–30. September 2005 an der Technischen Universität Berlin. Kolloquiumsbeiträge)

Preface - Peckhaus, Volker; Löwe, Benedikt; Räsch, Thoralf (Foundations of Formal Sciences IV. The History of the Concept of Formal Sciences)

Rankings und Evaluationen im Bildungsbereich. - Lück, Sonja; Kraft, Manfred (Genus oeconomicum. Ökonomie - Macht - Geschlechterverhältnisse)

Husserl, Edmund, "Philosophy of Arithmetik. Psychological and Logical Investigations with Supplementary Texts from 1887-1901", übers. u. hg. v. Dallas Willard, Kluwer: Dordrecht 2003 (Collected Works, Bd. 10) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Copeland, B. Jack, "The Essential Turing. Seminal Writings in Computing, Logic, Philosophy, Artificial Intelligence, and Artificial Life plus ‘The Secrets of Enigma’", Clarendon Press: Oxford 2004 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Bolzano, Bernard, "Briefe an František Príhonský (1824–1948)", 3 Bde., hg. v. Jan Berg (Bernard-Bolzano-Gesamtausgabe, R. III, 3, 1–3), Frommann-Holzboog: Stuttgart-Bad Cannstatt 2005 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Bolzano, Bernard, "Vermischte Mathematische Schriften 1832–1848, Teil 1", hg. v. Jan Berg (Bernard-Bolzano-Gesamtausgabe, R. II.A.11.1), Friedrich Frommann Verlag-Günther Holzboog: Stuttgart-Bad Cannstatt 2001 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Cassini, Alejandro, “Newton and Leibniz on Non-substantial Space”, In: Theoria. Segunda Epoca 20, Nr. 52 (2005), 25-42 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Lacki, Jan, “Styles of Physical Thinking Versus Mathematical Ones”, In: Synthese 134 (2003), 273-288 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Burgess, John P., “Mathematics and the Bleak House”, In: Philosophia Mathematics (3) 12 (2004), 18-36 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Burgess, John P, "Fixing Frege", Princeton University Press: Princeton, NJ 2005 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Floyd, Juliet/Shieh, Sanford (Hgg.), "Future Pasts. The Analytic Tradition in Twentieth-Century Philosophy. Dedicated to Burton Dreben", Oxford University Press: Oxford 2001 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Stöltzner, Michael, “On Optimism and Opportunism in Applied Mathematics. Mark Wilson meets John von Neumann on Mathematical Ontology”, In: Erkenntnis 69 (2004), 121–143 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Weigel, Erhard, "Universi corporis pansophici caput summum. Werke I", hg. u. eingel. v. Thomas Behme, Frommann-Holzboog: Stuttgart-Bad Cannstatt 2003 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

van Dalen, Dirk, "Mystic, Geometer, and Intuitionist. The Life of L.E.J. Brouwer, Vol. 2: Hope and Disillusion", Oxford University Press: Oxford 2005 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Hoffmann, Sarah, “Kitcher, Ideal Agents, and Fictionalism”, In: Philosophia Mathematica (3) 12 (2004), 3–17 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Weiner, Joan, "Frege Explained. From Arithmetic to Analytic Philosophy", Open Court: Chicago, IL 2004 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Gezielt fördern. Verben, Präpositionen, Adverbien, Konjunktionen. Arbeitsheft 5./6 - Breitkopf, Kathleen; Heinz, Hans Joachim; Niederhaus, Constanze; Plieninger, Martin

Martin, Donald A., “Gödel’s Conceptual Realism”, In: Bulletin of Symbolic Logic 11 (2005), 207–224 - Peckhaus, Volker (Mathematical Reviews)

Ehrlich, Philip, “The Rise of non-Archimedean Mathematics and the Roots of a Misconception. I. The Emergence of non-Archimedean Systems of Magnitudes”, In: Archives of the History of Exact Science 60 (2006), 1–121 - Peckhaus, Volker (Mathematical Reviews)

Tapp, Christian, "Kardinalität und Kardinäle. Wissenschaftshistorische Aufarbeitung der Korrespondenz zwischen Georg Cantor und katholischen Theologen seiner Zeit", Steiner: Stuttgart 2005 - Peckhaus, Volker (Mathematical Reviews)

Ewald, William, “Hilbert’s Wide Program”, in: Logic Colloquium 2000, Association for Symbolic Logic: Urbana 2005 (Lect. Notes Logic; 19), 228–251 - Peckhaus, Volker (Mathematical Reviews)

Eder, Ulrike: ,Auf die mehrere Ausbreitung der teutschen Sprache soll fürgedacht werden’: Deutsch als Fremd- und Zweitsprache im Unterrichtssystem der Donaumonarchie zur Regierungszeit Maria Theresias und Josephs II - Ptashnyk, Stefaniya (Studia Linguistica, Heft XXXI/2012. Wroclaw: Wydawnictwo Uniwersytetu Wroclawskiego)

Eder, Ulrike: „Auf die mehrere Ausbreitung der teutschen Sprache soll fürgedacht werden“: Deutsch als Fremd- und Zweitsprache im Unterrichtssystem der Donaumonarchie zur Regierungszeit Maria Theresias und Josephs II - Ptashnyk, Stefaniya (Studia Linguistica XXXI, Wroclaw 2012)

Quasiparticle corrections to the electronic properties of anion vacancies at GaAs(110) and InP(110) - Hedström, Magnus; Schindlmayr, Arno; Schwarz, Günther; Scheffler, Matthias (Physical Review Letters)
We propose a new method for calculating optical defect levels and thermodynamic charge-transition levels of point defects in semiconductors, which includes quasiparticle corrections to the Kohn-Sham eigenvalues of density-functional theory. Its applicability is demonstrated for anion vacancies at the (110) surfaces of III–V semiconductors. We find the (+/0) charge-transition level to be 0.49 eV above the surface valence-band maximum for GaAs(110) and 0.82 eV for InP(110). The results show a clear improvement over the local-density approximation and agree closely with an experimental analysis.

Elimination of the linearization error in GW calculations based on the linearized augmented-plane-wave method - Friedrich, Christoph; Schindlmayr, Arno; Blügel, Stefan; Kotani, Takao (Physical Review B)
This paper investigates the influence of the basis set on the GW self-energy correction in the full-potential linearized augmented-plane-wave (LAPW) approach and similar linearized all-electron methods. A systematic improvement is achieved by including local orbitals that are defined as second and higher energy derivatives of solutions to the radial scalar-relativistic Dirac equation and thus constitute a natural extension of the LAPW basis set. Within this approach linearization errors can be eliminated, and the basis set becomes complete. While the exchange contribution to the self-energy is little affected by the increased basis-set flexibility, the correlation contribution benefits from the better description of the unoccupied states, as do the quasiparticle energies. The resulting band gaps remain relatively unaffected, however; for Si we find an increase of 0.03 eV.

Dynamische Basisontologie und kooperative Semantiken. Möglichkeiten und Grenzen der Kombination begrifflicher und graphischer Wissensorganisation - Hagengruber, Ruth (HNI Jahresbericht)

Dynamic Ontology and Cooperative Semantics. The Combination of Conceptual and Graphical Knowledge Representation: Its Possibilities and Limits - Hagengruber, Ruth (HNI Annual Report)

Das Leseplakat. Eine Aufgabenstellung zur Rezeption vorgelesener Bücher - Kruse, Iris (Selbsttätigkeit und Aufgabenstellungen in der Grundschule. Grundschulunterricht)

Unterrichtliche Förderung auf der semantisch-lexikalischen Sprachebene: Didaktische Implikationen einer epigenetischen Entwicklungstheorie - Albers, Timm (Heilpädagogik Online)

Informelle Lernkontexte in der schulischen Sprachförderung - Albers, Timm; Mußmann, Jörg (Rundbrief der dgs Landesgruppe Niedersachsen)

Tiere in Afrika: Förderung semantisch-lexikalischer Sprachkompetenzen im Unterricht - Albers, Timm (Zeitschrift für Heilpädagogik)
Keywords: s2n; Scan2Net

Denken in Darstellungen – Schiller und die Geschichte - Süßmann, Johannes (Schiller und die Geschichte)

[Art.] Geschichtswissenschaft - Süßmann, Johannes (Enzyklopädie der Neuzeit, Bd. 4)

Fallstudien. Theorie – Geschichte – Methode. Internationale Konferenz (gefördert von der DFG). Bericht zur Tagung. Frankfurt am Main, 15.–17. September 2005 - Engel, Gisela; Scholz, Susanne; Süßmann, Johannes
Keywords: Fallgeschichte

Veränderung der Schulfreude von der Grundschule zur weiterführenden Schule - Bloh, Bea; Schürer, Sina (Risikofaktoren kindlicher Entwicklung. Migration, leistungsbezogene Emotionen und der Übergang von der Grundschulzeit zu den weiterführenden Schulen.A.)

Wie Schülerinnen und Schüler den Wechsel von der Grundschule zur weiterführenden Schule erleben – ein Zwischenbericht. - van Ophuysen, Stefanie; Bloh, Bea; Schürer, Sina (Forum Schule)

Veränderung von Schülermerkmalen in der Übergangsphase von der Grundschule zur weiterführenden Schule - Bloh, Bea; van Ophuysen, Stefanie; Schürer, Sina

Die Schulformentscheidung aus Elternsicht. Eine Untersuchung der zur Ablehnung der Schulformempfehlung am Ende der Grundschulzeit - Bloh, Bea

Schulformentscheidung am Ende der Grundschulzeit: Warum Eltern die Empfehlung nicht wahrnehmen - Bloh, Bea; van Ophuysen, Stefanie

Das Erleben des Übergangs in Abhängigkeit der Schulformempfehlung - van Ophuysen, Stefanie; Bloh, Bea

Veränderung der Schulfreude von der Grundschule zur weiterführenden Schule - Bloh, Bea; Schürer, Sina (Risikofaktoren kindlicher Entwicklung. Migration, leistungsbezogene Emotionen und der Übergang von der Grundschulzeit zu den weiterführenden Schulen)

Übergangsgestaltung durch schulstufenübergreidende Lehrerkooperation - Schürer, Sina; Bloh, Bea; van Ophuysen, Stefanie (Professionelles Handeln in der Grundschule: Entwicklungslinien und Forschungsbefunde)

Sociolinguistic Implications of Narratology: Focalization and ‘Double Deixis’ in Conversational Storytelling - Mildorf, Jarmila (The Travelling Concept of Narrative)

Disenchanting the World, Enchanting the Reader: The Negotiation of Biochemistry in Sinclair Lewis’ 'Arrowsmith' - Mildorf, Jarmila (Magic, Science, Technology, and Literature)

Introduction - Seeber, Hans Ulrich; Mildorf, Jarmila; Windisch, Martin (Magic, Science, Technology, and Literature)

Book review: Alan Palmer (2004). Fictional Minds. Lincoln: University of Nebraska Press - Mildorf, Jarmila (Anglia)

Nachruf auf Clotilde Schlayer - Schönhärl, Korinna (George-Jahrbuch)

Efficient Control of Formation Flying Spacecraft - Dellnitz, M.; Junge, O.; Krishnamurthy, A.; Ober-Blöbaum, Sina; Padberg, K.; Preis, R. (Friedhelm Meyer auf der Heide and Burkhard Monien, editors, New Trends in Parallel & Distributed Computing)

Optimal reconfiguration of formation flying spacecraft - a decentralized approach - Junge, O.; Marsden, J.E.; Ober-Blöbaum, Sina (45th IEEE Conference on Decision and Control)

DFG-Projekt RealTest - Test und Zuverlässigkeit nanoelektronischer Systeme - Becker, Bernd; Polian, Ilia; Hellebrand, Sybille; Straube, Bernd; Wunderlich, Hans-Joachim (it - Information Technology)

Johnsons Beschäftigung mit den Medien - van Laak, Lothar (So noch nicht gezeigt. Uwe Johnson zum Gedenken. London 2004)

Episierung des Romans durch den Film. Uwe Johnsons Jahrestage in der Fernsehverfilmung Margarethe von Trottas - van Laak, Lothar (Kontext Film. Beiträge zu Literatur und Film)

Rezension zu: Norm Green & Kathy Green (2005): Kooperatives Lernen im Klassenraum und im Kollegium. Das Trainingsbuch - Kullmann, Harry (Die Deutsche Schule)

„Ordnung und Überschreitung in mittelhochdeutschen Minnereden. ‚Der Minne Gericht‘ des Ellenden Knaben“ - Egidi, Margreth (Triviale Minne? Konventionalität und Trivialisierung in spätmittelalterlichen Minnereden (Quellen und Forschungen zur Literatur u. Kulturgesch. 40 [274]))

Minnelied und Sangspruch im Kontext der Überlieferung: Gattungen als Zuschreibungsphänomene“ - Egidi, Margreth (Wolfram-Studien 19. Text und Text in lateinischer und volkssprachiger Überlieferung des Mittelalters. Freiburger Kolloquium 2004, in Verbindung mit Wolfgang Haubrichs u. Klaus Ridder)

Trends and styles in visual masking. - Scharlau, Ingrid; Ansorge, Ulrich; Breitmeyer, Bruno G. (Advances in Cognitive Psychology)
The topic of the present edition is visual masking paradigms-as powerful tool for demonstrating the processing of nonconscious visual information. In the present issue one article presents an improved methodology for disentangling perceptual and temporal influences in markers. Another paper demonstrates that preemptive control, or DPS, mediates the allocation of attention towards possible targets. One of the contributions specify conditions under which DPS-like effects are found as opposed to conditions under which stimulus-driven effects are found. A study of two illusions which the prime may cause in a trailing stimulus, a temporal pre-dating of the mask and a perception of motion in later stimuli adjacent to the prime is presented in the issue. Another contribution addresses how the percept of a stimulus is altered by a temporal and spatial interplay of two backward masks or of one forward mask and two backwards masks. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: visual masking; visual information; attention; stimulus-driven effects; motion perception; Attention; Illusions (Perception); Motion Perception; Visual Masking

Latency facilitation in temporal-order judgments: Time course of facilitation as a function of judgment type. - Scharlau, Ingrid; Ansorge, Ulrich; Horstmann, Gernot (Acta Psychologica)
The paper is concerned with two models of early visual processing which predict that priming of a visual mask by a preceding masked stimulus speeds up conscious perception of the mask (perceptual latency priming). One model ascribes this speed-up to facilitation by visuo-spatial attention [Scharlau, I., & Neumann, O. (2003a). Perceptual latency priming by masked and unmasked stimuli: Evidence for an attentional explanation. Psychological Research 67, 184-197], the other attributes it to nonspecific upgrading mediated by retino-thalamic and thalamo-cortical pathways [Bachmann, T. (1994). Psychophysiology of visual masking: The fine structure of conscious experience. Commack, NY: Nova Science Publishers]. The models make different predictions about the time course of perceptual latency priming. Four experiments test these predictions. The results provide more support for the attentional than for the upgrading model. The experiments further demonstrate that testing latency facilitation w
Keywords: latency facilitation; temporal order judgments; visual processing; priming; conscious perception; visual mask; Adult; Attention; Female; Humans; Judgment; Male; Perceptual Masking; Reaction Time; Space Perception; Time Perception; Visual Perception; Consciousness States; Judgment; Priming; Visual Masking; Temporal Order (Judgment)

More efficient rejection of happy than of angry face distractors in visual search. - Horstmann, Gernot; Scharlau, Ingrid; Ansorge, Ulrich (Psychonomic Bulletin & Review)
In the present study, we examined whether the detection advantage for negative-face targets in crowds of positive-face distractors over positive-face targets in crowds of negative faces can be explained by differentially efficient distractor rejection. Search Condition A demonstrated more efficient distractor rejection with negative-face targets in positive-face crowds than vice versa. Search Condition B showed that target identity alone is not sufficient to account for this effect, because there was no difference in processing efficiency for positive- and negative-face targets within neutral crowds. Search Condition C showed differentially efficient processing with neutral-face targets among positive- or negative-face distractors. These results were obtained with both a within-participants (Experiment 1) and a between-participants (Experiment 2) design. The pattern of results is consistent with the assumption that efficient rejection of positive (more homogenous) distractors is an im
Keywords: angry face distractors; visual search; negative face distractors; Adult; Anger; Attention; Face; Female; Happiness; Humans; Male; Rejection (Psychology); Visual Perception; Distraction; Face Perception; Visual Perception; Visual Search